2016
DOI: 10.15403/jgld.2014.1121.251.chp
|View full text |Cite
|
Sign up to set email alerts
|

Secretin-enhanced Magnetic Resonance Cholangiopancreatography in Pancreatic Insufficient and Pancreatic Sufficient Cystic Fibrosis Patients

Abstract: Background & Aims: Although indirect methods of assessment of the exocrine pancreatic function have become the standard of care in the monitoring of pancreatic status, it still remains a current clinical challenge. Our aim was to compare the width of the pancreatic duct in pancreatic insufficient (PI) and pancreatic sufficient (PS) cystic fibrosis (CF) patients using secretin-enhanced magnetic resonance cholangiopancreatography (SE-MRCP). Methods: Thirty-seven CF patients were enrolled for this cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…11 Following endotherapy (sphincterotomy/stone extraction/stenting) in patients with CP, increases in pancreatic flow output and total excreted volume have been demonstrated. 10 Applications to other conditions associated with pancreatic insufficiency such as cystic fibrosis have found limited value in the use of post-secretin main pancreatic duct diameter as a marker of disease severity, 15 but demonstrated qualitatively reduced post-secretin excreted volume in patients with more advanced disease. 16 Quantitative MRCP studies in this cohort have not been reported.…”
Section: Diffuse Pancreatic Diseasementioning
confidence: 99%
“…11 Following endotherapy (sphincterotomy/stone extraction/stenting) in patients with CP, increases in pancreatic flow output and total excreted volume have been demonstrated. 10 Applications to other conditions associated with pancreatic insufficiency such as cystic fibrosis have found limited value in the use of post-secretin main pancreatic duct diameter as a marker of disease severity, 15 but demonstrated qualitatively reduced post-secretin excreted volume in patients with more advanced disease. 16 Quantitative MRCP studies in this cohort have not been reported.…”
Section: Diffuse Pancreatic Diseasementioning
confidence: 99%
“…One study was able to demonstrate the dynamics of postprandial pancreatic duct secretions by the use of MRI combined with a selective inversion-recovery pulse [ 12 ]. Another recent study evaluated s-MRI in CF patients focusing on the pancreatic duct dilatation, demonstrating poor diagnostic accuracy [ 13 ]. High costs and technical complexity of the analysis are factors that may limit the feasibility of s-MRI in a routine clinical setting.…”
Section: Introductionmentioning
confidence: 99%